Budidaya Tanaman Obat Keluarga untuk Mengaktualisasi Program Go Green di SMA Plus Cendikia Cikeas - Maya Fadhillah; Shafa Noer; Endah Diah Parwati; Jasmin Aulia Nurrohmah; Ranti Ranti (Lembaga Pengembangan Kinerja Dosen, 2024)
Community service is carried out at SMA Plus Cendikia Cikeas located in Gunung Putri, Bogor by cultivating Family Medicinal Plants (TOGA). It is hoped that TOGA cultivation can be a solution to the problem of actualizing Go Green schools. The achievement of this activity is that the school community (students, teachers and school employees) can increase their knowledge about TOGA, how to plant it, its name and benefits as well as the existence of a green area in the form of TOGA in the school environment. The method used is a participatory approach by providing education and procedures for planting family medicinal plants. The stages of this activity are 1) preliminary stage, 2) TOGA socialization stage, and 3) planting stage. Plants that have been planted are labeled with their names on the nameplate. This activity went well, starting from providing a small educational seminar on TOGA planting tutorials to providing nameplates. The results obtained from this activity are empty space that has not been utilized as a TOGA park. Further cultivation is carried out by partners to create a green school (go green).